The epidemiology, clinical characteristics and associated risk factors of injuries in crossfit athletes : a prospective cohort study - Viljoen, Carel Thomas (University of Pretoria, 2024)
Thesis (MSc (Physiotherapy))--University of Pretoria, 2023.